Ten years of “Condensed Matter Physics” (Condensed Matter Physics, 2003)
This year the journal “Condensed Matter Physics” celebrates its tenth anniversary.
It was founded in 1993 by the Institute for Condensed Matter Physics of the
National Academy of Sciences of Ukraine for the purpose of publishing the regular
and review papers in the field of statistical mechanics and condensed matter theory.